Vowel acoustics of Nungon child-directed speech, adult dyadic conversation, and foreigner-directed monologues - Sarvasy, Hannah S.; Li, Weicong; Elvin, Jaydene; Escudero, Paola (Frontiers in Psychology, 2022)
In many communities around the world, speech to infants (IDS) and small children (CDS) has increased mean pitch, increased pitch range, increased vowel duration, and vowel hyper-articulation when compared to speech directed to adults (ADS). Some of these IDS and CDS features are also attested in foreigner-directed speech (FDS), which has been studied for a smaller range of languages, generally major national languages, spoken by millions of people. We examined vowel acoustics in CDS, conversational ADS, and monologues directed to a foreigner (possible FDS, labeled MONO here) in the Towet dialect of the Papuan language Nungon, spoken by 300 people in a remote region in northeastern Papua New Guinea. Previous work established that Nungon CDS entails optional use of consonant alteration, special nursery vocabulary, and special morphosyntax. This study shows that Nungon CDS to children aged 2;2–3;10 lacks vowel hyper-articulation, but still displays other common prosodic traits of CDS styles around the world: increased mean pitch and pitch range. A developmental effect was also attested, in that speech to 2-year-olds contained vowels that were significantly longer than those in speech to 3-year-olds, which in turn had vowels of similar duration to those in Nungon ADS. We also found that Nungon FDS vowel triangles, measured from monologues primarily directed to a non-native speaker, were significantly larger than those of either CDS or conversational ADS, indicating vowel hyper-articulation. The Nungon pattern may align with the patterns of vowels in Norwegian IDS, CDS, and FDS, where hyper-articulation is found in FDS, but not CDS or IDS. The languages of the New Guinea area constitute 20% of the world's languages, but neither an acoustic comparison of vowels in CDS and ADS, nor an acoustic study of FDS, has previously been completed for any language of New Guinea. The function of an FDS style in a small, closed community like those of much of New Guinea may differ from that in larger societies, since there are very few non-native speakers of Nungon. Thus, this study uses monologues recorded with a foreign researcher as interlocutor to study Nungon FDS.